Characterization of a haemolymph storage protein and its relationship to insect weight and development in the European corn borer, Ostrinia nubilalis Hubner (Lepidoptera:Pyralidae). - McKee, Susan Elaine. (University of Ottawa (Canada), 1996)
In this study I identified and characterized a storage protein in the European corn borer, Ostrinia nubilalis. The protein was identified as a storage protein by its native molecular weight of approximately 500 kDa and the observation that it increased in abundance throughout larval development and diminished with adult development. The protein had the characteristics of an arylphorin-like storage protein because it is a heterohexamer and is the most abundant protein in the haemolymph, increasing to the intermoult period with a decline just prior to pupation. Larval weight accounts for much of the variation in storage protein levels in the fat body (90%) and intact larvae (80%). Similar results were found with larval age and storage protein levels (80% for both fat body and intact larvae). Since nutrition has been proposed as a regulator of storage protein levels, I examined the relationship between storage protein levels, protein quality in the diet and larval weight. There was no significant effect of protein quality in the diet on storage protein levels after correcting for the weight of the larvae. Finally, I examined how development was affected by protein quality in the insect's diet. Corn borers fed poorer diets could compensate by consuming more and increasing their larval duration, however, they did so at lower pupal weights than those corn borers on the standard diet. Logistic regression analysis showed that pupal weight had a significant effect on survival, suggesting that heavier pupae are more likely to survive to the adult stage than lighter pupae. (Abstract shortened by UMI.)
Keywords: Biology, Entomology.